The Belt and Road Initiative: Analysis of Twitter Communication During Second Belt and Road Forum for International Cooperation - Nosharwan Arbab Abbasi; Dianlin Hunag; Furqan Rao (National University of Modern Languages (NUML), Islamabad, 2021)
China's Belt and Road Initiative (BRI), also known as One Belt, One Road (OBOR), was launched in 2013 by President Xi Jinping. BRI opens "gateway to opportunities" and establishes a new grand geopolitical strategy for regional development, international economic cooperation and new world order. To foster BRI, China hosted the second Belt and Road Forum for International Cooperation (BRF) in Beijing on 25-27 April 2019. New media tools including dedicated web pages and social media sources were utilised to promote the BRF 2019. Particularly, Twitter was used by government and media organizations to promote and share the proceedings of the event. Topics related to Belt and Road Initiative were trending on social media resulting in a wide reach and engagement. A large number of pertinent tweets appeared with trending hashtags such as #brf2019, #BeltandRoad and #BRI. Major contribution to this tweet activity came from politicians, government officials and media groups. This study analyses the trending hashtags #brf2019 and #BeltandRoad (N=20,727) on Twitter on the occasion of second BRF 2019 to understand the patterns of Twitter data. Specifically, this study attempts (1) to investigate how Twitter was used by media groups to promote the second Belt and Road Forum; (2) to identify top influencers to promote the second Belt and Road Forum; (3) to analyse overall sentiment towards the second Belt and Road Forum. The study follows mixed method for Social Media performance data by combining qualitative content analysis and sentimental analysis of tweets. All the tweets collected were publicly posted and were tracked using Twitter streaming API and Python programming language. For analysis, parameters such as; users, reach, impression, engagement, type of tweet, trending topics, source of tweets and main themes were analysed.